Enhancing Photosynthetic Characterization and Biomass Productivity of Nannochloropsis Oceanica by Nuclear Radiation - Lu, Hongxiang; Cheng, Jun; Wang, Zhenyi; Zhang, Xiangdong; Chen, Shutong; Zhou, Junhu (Frontiers in Energy Research, 2020)
Microalgae with a high growth rate and a carbon fixation rate present a promising potential to produce diverse renewable energy products and reduce greenhouse gas emissions. However, some microalgal species may have limited light-use efficiency and specific growth rate. To alleviate these issues, Nannochloropsis oceanica was subjected to 137Cs–γ radiation to obtain the desired mutant with enhanced light-use efficiency and increased biomass productivity. The N. oceanica mutant ZJU700 showed a 26.7% increase in biomass productivity after nuclear irradiation at a 700 GY dosage. It was found that the mutant had a 30.2% higher oxygen evolution rate than the wild type cells. High-throughput transcriptome sequencing showed that expression of photosynthetic related genes in the mutant were much higher than in wild type cells. Expression of the psbO gene increased by 455% in mutant ZJU700, contributing to an increased oxygen evolution rate by splitting water. Three up-regulated genes, namely petC, petF, and petH, resulted in enhanced electron transport during the photoreaction process. Up-regulation of many genes involved in the Calvin cycle indicated that CO2 fixation rate was likely to be increased to produce more carbohydrates in mutant, thereby contributing to the increased biomass productivity in mutant ZJU700.